Deformation partitioning at the rupture front in NW Himalaya: evidence from tectono-geomorphic and paleoseismic investigations - Pandey, Anand K; Pandey, Prabha; Singh, Guru Dayal; Prasad, GV Ravi; Dutta, K; Ray, DK (Himalayan Journal of Sciences, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> DOI = 10.3126/hjs.v5i7.1290 Himalayan Journal of Sciences Vol.5(7) (Special Issue) 2008 p.97